The features of diagnostics of grain crop seeds intended for export - E. R. Ruchkov; D. I. Shukhin; A. A. Kuznetsova; M. B. Kopina (Зерновое хозяйство России)
Russia occupies a leading position among the largest wheat producers and exporters. One of the key requirements for the biological safety of domestic grain products is the phytosanitary requirements of importing countries. The conformity of grain products with regard to phytopathogenic micromycetes is determined by their complete absence or the minimum content in the batch. When shipping exported products, it is necessary to carry out a phytosanitary estimation of a batch of plant products in a short time. In the current paper there has been estimated the effect of the proposed method of sample preparation of grain crop seeds on the quality of an isolated fungal pathogens’ DNA. The purpose of the study was to optimize the methods of sample preparation of grain products for the extraction of nucleic acids with further identification to reduce laboratory trials. The development of modern, reliable and low labor-consuming methods for diagnosing phytopathogens in plant products is of great urgency. In order to conduct the current research, wheat, barley and rye kernels were artificially inoculated with such fungal pathogens as Parastagonospora nodorum, the causative agent of Septoria leaf spot, and Alternaria infectoria, the causative agent of Alternaria leaf spot. The infection was carried out by soaking the kernels in a spore suspension followed by incubation. In order to assess infection, there were used the classical methods of mycology, as well as the patented E.Yu. Toropova’s method. The pathogens were identified by a classical PCR analysis using the target-specific primers. There has been given an assessment of the sensitivity of the proposed extraction method for each of the studied crops. The method allows identifying target objects even with a minimum number of infected kernels in the sample (1–5 infected seeds per 195–199 healthy ones). There were not identified any related pathogens, and there were no false-positive results during the conducted PCR analysis.